Molecular and Macromolecular Changes in Bottle-Aged White Wines Reflect Oxidative Evolution–Impact of Must Clarification and Bottle Closure - Coelho, Christian; Julien, Perrine; Nikolantonaki, Maria; Noret, Laurence; Magne, Mathilde; Ballester, Jordi; Gougeon, Régis D. (Frontiers in Chemistry, 2018)
Chardonnay wines from Burgundy, obtained from musts with three levels of clarification (Low, Medium and High) during two consecutive vintages (2009 and 2010) and for two kinds of closures (screw caps and synthetic coextruded closures) were analyzed chemically and sensorially. Three bottles per turbidity level were opened in 2015 in order to assess the intensity of the reductive and/or oxidative aromas (REDOX sensory scores) by a trained sensory panel. The chemical analyses consisted in polyphenols and colloids quantification, followed by a proteomic characterization. For the two vintages, the REDOX sensory scores appeared to be driven both by the type of closure and to a lesser extent by the level of must clarification. Vintages and must racking prefermentative operations were also distinguished by chemical analyses. All white wines from the lowest must turbidity had the lowest REDOX sensory scores. Such wines exhibited lower concentrations in tyrosol and grape reaction product and higher concentrations in colloids with relatively low molecular weights. Among these macromolecules, grape proteins were also quantified, two of them exhibiting concentrations in bottled wines, which were statistically correlated to oxidative evolution in white wines